All‐Textile Triboelectric Generator Compatible with Traditional Textile Process. Issue 9 (24th October 2016) - Zhang, Lushuai; Yu, Yanhao; Eyer, Gregory P.; Suo, Guoquan; Kozik, Liz Anna; Fairbanks, Marianne; Wang, Xudong; Andrew, Trisha L.
Abstract : All‐textile triboelectric generators (TEGs) allow for seamless integration of TEGs into garments, while maintaining the intrinsic flexibility, breathability, durability, and aesthetic value of normal textiles. However, practical approaches to construct fabric TEGs using traditional textile processes, such as sewing, weaving, and knitting, are underreported. In this work, two approaches to create an all‐textile TEG using straight‐forward textile manufacturing methods are presented. The first approach is to assemble two different cloths of opposite surface charge characteristics in a face‐to‐face configuration. A cotton fabric functionalized with fluoroalkylated polymeric siloxanes is necessary to generate usable triboelectric power output, when coupled with a pristine nylon cloth. The increased surface charge density by introducing fluoroalkyl groups is confirmed by Kelvin probe force microscopy measurements. The second approach is to weave or knit together two different conductive threads of opposite surface charge characteristics to create a monolithic triboelectric textile. The weave or knit pattern used to assemble this textile directly controls the density of contact points between the two types of threads, which, ultimately, determines the areal triboelectric power output of the textile. Overall, two feasible methods for constructing unprecedented textile‐based triboelectric generators with notable power output are presented. Abstract : Funtional all‐textile triboelectric generators are constructed by using simple traditional textile processes, such as sawing, knitting and weaving. Our fabrication methods fill the gap between the pursuit of wearable power supplies and the lack of practical methods to truly integrate sophisticated electronic devices into garments, while maintaining the natural feel and look of normal textile.